Cyclotorsion Measurement on Scanning Laser Ophthalmoscopy Imaging Compared With Fundus Photography in Patients With Fourth Nerve Palsy and Healthy Controls: CySLO-IV Study. Issue 4 (19th December 2021) - Kanku, Madeleine S.; Sele, Silvano; Held, Ulrike; Jaggi, Gregor P.; Landau, Klara; Traber, Ghislaine L.
Abstract : Background: The purpose of the study is to evaluate the agreement of the foveopapillary angle (FPA) on conventional fundus photography (c-FPA) with the FPA on scanning laser ophthalmoscopy (SLO) imaging (SLO-FPA) in patients with fourth nerve palsy and healthy controls (HCs). Methods: The FPA was measured in both eyes of 25 patients and 25 HCs in synedra View (c-FPA) and with the integrated algorithm of the Heidelberg Spectralis OCT (SLO-FPA). The primary endpoint was the agreement of both measurements. Furthermore, we evaluated the influence of the eye tracker, the influence of fixation on objective torsion, and the FPA cutoff between patients and HCs. Results: The mean SLO-FPA in patients (6/25 acquired palsies) was 11.3 ± 3.6° and 6.4 ± 2.1° in HCs. The mean c-FPA was 11.4 ± 4.0° and 5.8 ± 2.2°, respectively. The Bland–Altman plot of c-FPA vs SLO-FPA in patients and HCs shows no systematic bias (mean of −0.28°). Limits of agreement were −6.58 and 6.02°. Using the eye tracker had no systematic effect. There was no evidence for an immediate shift of torsion with change of fixation (24/25 patients and 23/25 HCs). Discrimination between patients and HCs by the SLO-FPA is very good with an area under the curve = 0.92 (95% confidence interval: 0.84–0.99). Conclusions: SLO-FPA measurement allows convenient and consistent assessment of objective cyclotorsion. There was no systematic bias in the difference between SLO-FPA and traditional c-FPA; thus, SLO-FPA is a valuable alternative to the commonly used c-FPA. Using the eye tracker is recommended for proper centering of the ring scan.